The Effects of Income and Consumption Tax Regimes and Future Tax Rate Uncertainty on Proportional Savings and Risk-Taking - Meade, Janet A. (The Accounting Review, 1995)
[This paper uses an experimental design to examine how income and consumption tax regimes and future tax rate uncertainty affect proportional savings and risk-taking. For the experiment, undergraduate subjects were given certificates redeemable for goods and services at two time periods. They were then asked to determine the time at which they wished to redeem the certificates and the manner in which they wished to allocate unredeemed certificates between safe and risky investment funds. The results indicate that when future tax rates are certain, an income tax regime reduces proportional savings and increases proportional risk-taking when compared to a consumption tax regime. When future tax rates are uncertain, the effects are more complex. They generally suggest, however, that future tax rate uncertainty adversely affects the savings and risk-taking neutrality of a consumption tax regime while diminishing the risk-taking incentive of an income tax regime.]